PENGARUH KEPEMIMPINAN TERHADAP KINERJA KARYAWAN ISLAMI MELALUI KOMITMEN PEGAWAI PADA USAHA PONDOK PESANTREN DI GRESIK - Ari Prasetyo (Jurnal Ilmu Manajemen, 2022)
The central role of leadership in boarding schools and its relevance in the economic development of boarding schools through the efforts of boarding school cooperatives still need to be studied. This research aims to analyze the influence of influential leadership on employee commitment, employee commitment on the performance of Islamic employees, and leadership on the performance of Islamic employees on business ventures managed by boarding schools. The research method used is causal. The sample is 100 respondents. The Independent variable used is Islamic leadership. The intervening variable used is employee commitment. The dependent variable is Islamic employee performance. The data collection technique is a survey. The analysis technique used in this research is Structural Equation Modeling with SmartPLS (Partial Least Square) program. The results show that leadership has a significant effect on employee commitment. Leadership significantly affects the performance of Islamic employees in boarding school cooperatives. In contrast, employee commitment does not significantly affect the performance of Islamic employees in boarding school cooperatives. Good leadership will help cooperatives to get employee performance which will ultimately have a good impact on business performance. In addition, good leadership will help increase commitment. Even though commitment does not affect employee performance in this research, it is essential to create an employee program to increase their commitment toward boarding school cooperatives.